Targeted next‐generation sequencing reveals molecular heterogeneity in non‐chronic lymphocytic leukemia clonal B‐cell lymphocytosis. Issue 5 (19th August 2020) - Defrancesco, Irene; Zibellini, Silvia; Boveri, Emanuela; Frigeni, Marco; Ferretti, Virginia Valeria; Rizzo, Ettore; Bonometti, Arturo; Capuano, Francesca; Candido, Chiara; Rattotti, Sara; Tenore, Annamaria; Picone, Cristina; et al.
Abstract: Non‐chronic lymphocytic leukemia (non‐CLL) clonal B‐cell lymphocytosis (CBL) encompasses a heterogeneous group of hematologic disorders that are still poorly understood. To shed light on their biological aspects, we retrospectively analyzed a highly selected series of 28 patients, who had a clonal B‐cell population in the peripheral blood and in the bone marrow, without evidence of lymphoma. Extended targeted next‐generation sequencing revealed wide molecular heterogeneity with MYD88 (14%), PDE4DIP (14%), BIRC3 (11%), CCND3 (11%), NOTCH1 (11%), and TNFAIP3 (11%) as the most mutated genes. Mutations of MYD88 were "nonclassic" in most cases. Although some genetic lesions were overlapping with indolent lymphomas, mainly splenic B‐cell lymphomas of marginal zone origin and splenic diffuse red pulp small B‐cell lymphoma, the genetic profile of our non‐CLL CBL series seemed to suggest that various pathways could be involved in the pathogenesis of these disorders, not mirroring any specific lymphoma entity. These data better enlighten the molecular characteristics of non‐CLL CBL; however, more efforts are needed in order to improve the diagnostic process, prognostication, and clinical management.